First Prenatal Case of Genotypically and Phenotypically Overlapping Double Molecular Diagnosis of Van den Ende–Gupta and 22q11.2 Deletion Syndromes - Caroline Racine; Aurore Garde; Olivia Martz; Hana Safraou; Vinciane Eluard; Thierry Rousseau; Nathalie Marle; Fara T. Harizay; Laurent Martin; Julien Maraval; Ange‐Line Bruel; Christophe Philippe; et al. (Molecular Genetics & Genomic Medicine)
ABSTRACT Background Multiple molecular diagnoses (MMD) involve distinct or overlapping phenotypes. They are not so rare in the field of congenital anomalies, given an overall 3.5%–8% rate. Mainly, MMD imply distinct genotypes. Exceptionally, genotypes are linked, involving a causal CNV by itself, facing a SNV for a recessive disorder resulting in a dual diagnosis. Methods An unrelated couple was referred at 21 + 3 weeks of gestation for talipes equinovarus, cerebellar hypoplasia, clenched fists, elevated hemidiaphragm, and micrognathia. Chromosomal microarray and exome sequencing analyses were performed. Results Both identified a pathogenic de novo 22q11.21 deletion (22q11.2del). Fetal autopsy revealed additional features (postaxial polydactyly, facial features, and abnormal lung lobulation), atypical for 22q11.2del syndrome. At the clinician's request, exome sequencing reanalysis identified a paternally inherited SCARF2 variant, in trans to the 22q11.2del causing autosomal recessive Van den Ende–Gupta syndrome. This dual diagnosis explains the entire fetus phenotype. Discussion This is a novel case of dual diagnosis, first prenatal and second case of this ultrarare association. It reflects the crucial role of precise phenotypic description, combined with the importance of considering dual diagnosis in case of atypical clinical presentation. Finally, prenatal phenotypes remain a challenge given the paucity of available known prenatal data for most rare diseases. Trial Registration ClinicalTrial.gov ID: NCT05182242